A Study on the Characteristics of Proportional Control of Roll Screen Dampers’ Constant Air Volumes - Cho, Dong-Hyun; ., . (International Journal of Engineering and Technology, 2026)
In the present study, a new damper system using new technologies with a folding roll screen blade system was constructed. In addition, intelligent folding roll screen blades that can control the constant air volume in proportion to damper opening were constructed. Furthermore, an actuator was installed on a slim folding roll screen damper to construct an applied technology so that the constant air volume can be controlled in proportion to damper opening and closing in order to conduct an experimental study. As a result of the present study, the error rate between the theoretical air flow rate and the experimental air flow rate was in a range of ± 3%.The air flow rate increased linearly following the increase in damper opening. The air volume that passed through the roll screen damper increased in proportion to the static pressure and damper opening so that the air volume was controlled in proportion to the constant air volume.The simulation was conducted with damper opening degrees of 40%, 60% and 85 and according to the results, the damper outlet air volume was 158.2 m3/min when the opening was 40%, 223.7 m3/min when the opening was 60%, and 302.5m3/min when the opening was 80%. These simulation results were in good agreement with the experimental values.
Keywords: Damper. Roll Screen; Constant; Volume; Proportional Control; Screen Blade